Semantic enterprise application integration for business processes service-oriented frameworks - Mentzas, Gregoris, 1960-; Friesen, Andreas; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
The lack of formal semantics of applications and services to be integrated into business processes makes it difficult for software engineers and developers to interconnect heterogeneous applications. This book provides methods that incorporate and streamline processes that allow employees, decision makers, and industry partners to readily access corporate and customer data independent of where it resides. It provides the latest research findings in the design and development of business processes for academicians, researchers, and practitioners.
Collaboration Across the Enterprise: An Ontology Based Approach for Enterprise Interoperability / Aggelos Liapis, Stijn Christiaens -- Dynamic Data Mediation in Enterprise Application Integration Scenarios / Thanasis Bouras, Panagiotis Gouvas, Gregoris Mentzas -- Ontology-based Patterns for the Integration of Business Processes and Enterprise Application Architectures / Veronica Gacitua-Decar, Claus Pahl -- Agent-Driven Semantic Interoperability for Cross-Organisational Business Processes / Ingo Zinnikus, Christian Hahn, Klaus Fischer Germany -- The Semantic Side of Service-Oriented Architectures / Catarina Ferreira da Silva ... [et al.] -- Supporting Semantically Enhanced Web Service Discovery for Enterprise Application Integration / Dimitrios Kourtesis, Iraklis Paraskakis -- Light-Weight Semantic Integration of Generic Behavioral Component Descriptions / Jens Lemcke -- Business Rules Enabled Semantic Service Discovery and Selection for B2B Integration / Andreas Friesen -- A Semantic Web Service Based Middleware for the Tourism Industry / Yildiray Kabak ... [et al.] -- Application of the FUSION Approach for Tool Assisted Composition of Web Services in Cross Organisational Environments / Spiros Alexakis ... [et al.] -- Semantic Business Process Management: A Case Study / Sebastian Stein ... [et al.].
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 19, 2010).
Keywords: Semantic integration (Computer systems); Enterprise application integration (Computer systems); Service-oriented architecture (Computer science); Management information systems; Cross-organizational business processes; Enterprise application architectures; Enterprise application integration; Enterprise interoperability; Light-weight semantic integration; Semantic interoperability; Semantic service discovery; Semantic Web service; Tourism industry; Web service discovery; Electronic books